(untitled) (Perspectivas em Ciência da Informação, 2023)
This paper aims to analyze the activity of two Brazilian tourism agencies in social media and the online behavior of their consumers. Natural language processing resources were used, supported by sentiment analysis and content analysis techniques. The main results show that there is a prevalence of positive comments on the companies’ pages, and companies are more responsive to users on pages that have a higher number of positive comments. There is also a tendency towards greater interaction by companies with user comments that express positive emotions.